2n+3=16-3n

Simple and best practice solution for 2n+3=16-3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n+3=16-3n equation:



2n+3=16-3n
We move all terms to the left:
2n+3-(16-3n)=0
We add all the numbers together, and all the variables
2n-(-3n+16)+3=0
We get rid of parentheses
2n+3n-16+3=0
We add all the numbers together, and all the variables
5n-13=0
We move all terms containing n to the left, all other terms to the right
5n=13
n=13/5
n=2+3/5

See similar equations:

| (3x-44)+4x+x=180 | | 3(x+2)-7+(2x=14) | | 9=b-10 | | 8y+2y+4y-2=5y | | X-12x+12=4-15x+9 | | y2+2y–2=0 | | -3/4d=15 | | 3x-4=3x+14 | | 3x-7+6x=38 | | -1/3(6n-9)+4(n+2)=0 | | 25=x/2-10 | | 12q-3q=3 | | 19.00+4.50x=10.00+5.75x | | 0.2=x/80+x | | 20y-14y=12 | | 21/3x-7/12=2x-3/2 | | 39−43+x=-46 | | 3x-5=4x-35 | | 17.5+q+R=32.5 | | 9x−1​∘​​=6x+58​∘​​=87​∘​​ | | -22+28−x=-30 | | -15=b-8 | | a^+a-12=0 | | |x-10|+5=24 | | 9(4b–1)=2(9b+3) | | -4=5(b-2) | | Y-2=(x-5) | | (3h+4=) | | x​2​​−12x+27=0x | | -24-4n=-(n+8)-1 | | 3x+5+7x-4=304 | | 5x/3+2x/3=7 |

Equations solver categories